CORPORATE GOVERNANCE BEST PRACTICES - FREDERICK D. LIPMAN, L. KEITH LIPMAN (John Wiley & Sons, Inc., Hoboken, 2006)
This book is intended to be a practical guide to best corporate governance practices for public, private (including family-owned businesses), and nonprofit organizations, using concrete real-life examples. Good corporate governance is important to private companies that wish to attract bank and other institutional financing and equity investors. Private family-owned businesses need good corporate governance to establish dispute resolution mechanisms to prevent family quarrels from harming the business, particularly after the founder has died or retired. Not-for-profit organizations need to practice good corporate governance in order to assure their contributors that their gifts will be well spent. The Sarbanes-Oxley Act of 2002 and accompanying Securities and Exchange Commission (SEC) and listing rules legally mandate minimum corporate governance practices for most public companies. This book will be helpful to boards of directors and management of public companies that want to engage in the best practices, not just minimum legal requirements. Public companies that engage in best practices will generally be more attractive to investors and will receive higher corporate governance ratings.